The Effect of reading from screen on the 5th grade elementary students' level of reading comprehension on informative and narrative type of texts [Ekrandan okumani{dotless}n 5. Si{dotless}ni{dotless}f öǧrencilerinin bilgilendirici ve öyküleyici metin türünde okuduǧunu anlama düzeylerine etkisi] - AYDEMİR, ZEYNEP (My University, 2013)
Digital medias that becomepopular through the development of technology have given a different functionality to read write experiences. The new conceptions such as reading from screen, e-literacy, digital text etc. have gained currency. The aim of the research was determined as the effect of reading from screen upon the levels of reading comprehension of the fifth grade elementary school students in the informative and narrative text types. In the study, the pretest-posttest control group design was used. The participants consisted of 60 students studying at an elementary school located in the central district of Sakarya. Totally six texts were chosen to utilize in the study and the participants in control group were assigned to read the printed materials, while others were reading the version of the same material from screen. The reading comprehension test developed by the researchers was used as an assessment instrument. In the evaluation of informative texts, the five WS and one H method were used in accordance with the constructivist approach that is one of the alternative evaluation approaches, while the questions were being prepared for the narrative texts, the story elements which are generally required to be found in a text, were used and the story map method was prepared accordingly. The analysis of the reading comprehension points was performed through three related evaluations regarding the text category and therefore, two-factor ANOVA was used. As a result, the levels of reading comprehension of the students who read the informative text from screen were significantly higher than others. Moreover, there was no significant difference between the students reading the narrative texts from screen and printed material in terms of the levels of reading comprehension. © 2013 Educational Consultancy and Research Center.
Keywords: Informative text; Narrative text; Reading comprehension; Reading from screen